Pengembangan Cakram RoMSI (Roda MP-ASI) Sebagai Media Edukasi Pemberian MP-ASI Bagi Ibu Bayi Usia 0-6 Bulan - Revayasta Ananda; Meti Megawati; Sariestya Rismawati (Jurnal Ilmiah Kesehatan, 2026)
The low level of maternal knowledge about the appropriate provision of complementary foods for infants aged 0-6 months remains a risk factor for inappropriate feeding practices, which can contribute to nutritional problems and child growth and development. This study aims to develop educational media in the form of RoMSI Discs as an aid in counseling on the provision of complementary foods for mothers of infants aged 0-6 months. This study used a Research and Development (R&D) approach. Validation results showed that the RoMSI Disc media obtained an average score of 86% from material experts and 92% from media experts, both in the "very appropriate" category. Small-scale product trials obtained an average score of 96.6% and large-scale trials obtained an average score of 93.4%. Respondents considered the media very helpful in understanding the correct provision of complementary foods and were categorized as "very appropriate." The RoMSI Discs were proven to be feasible in terms of material and design and effective as an educational medium for providing complementary foods for mothers of infants aged 0-6 months.